If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -6whena = 3 Solving 5a + -6aehnw = 3 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Reorder the terms: -3 + 5a + -6aehnw = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + 5a + -6aehnw = 0 The solution to this equation could not be determined.
| 8n-2=42 | | k^2+14k-53=-2 | | (n-6)*7=21 | | 24=5b+9 | | (n-10)*4=12 | | 4x^2-10x-9=0 | | p^2+8p+7=-5 | | 27-2+4(k+3)=8(-3k-4) | | 6a+2a=40 | | n*6=75 | | 2/4-2x=14 | | n-3=13 | | n+25=40 | | 2/3x=-4 | | n/6=9 | | 5(2x+5)=4(2x-6)+2x | | 4x+3(x-2)=20-5x-x | | 2x-2=-12x+13 | | 3(5x+2)-x=2(y-3) | | 3(x+6)=2(x+9)+x | | 3(2x+y)+5z=-1 | | -5x^2+5x+9=0 | | x2+10/5 | | 5x+70=4x+80 | | 6x-18=2x+2 | | 1/5a-1/5=-6 | | 15x-12=3x+4 | | 8=(x+9) | | 3x+8=20-x | | 6+9=x | | 3x+8=20-6 | | 6666666g=5 |